Should unemployment benefits decrease as the unemployment spell lengthens? - Tuomas Saarenheimo (Bank of Finland, 2001)
It has become a conventional wisdom in economic policy debate that in order to minimise adverse effects on employment, unemployment benefits should decrease with the unemployment spell.This paper, using a series of simple search models, shows that the theoretical result regarding the optimality of a declining unemployment benefit profile is largely a result of specific modeling assumptions and fails to hold in a more general setting.While any pure reduction of unemployment benefits always improves employment, a redistribution of unemployment benefits from the long-term unemployed in favour of the short-term unemployed can either increase or decrease unemployment and unemployment benefit expenditure.The direction of the effect depends, inter alia, on the structure of unemployment and on the extent to which employed workers can reduce their lay-off probability.
URN:NBN:fi:bof-20140807590
Keywords: 330